A Review of the U.S. Global Change Research Program's Draft Strategic Plan - National Research Council (The National Academies Press, 2012)
The U.S. government supports a large, diverse suite of activities that can be broadly characterized as "global change research." Such research offers a wide array of benefits to the nation, in terms of protecting public health and safety, enhancing economic strength and competitiveness, and protecting the natural systems upon which life depends. The U.S. Global Change Research Program (USGCRP), which coordinates the efforts of numerous agencies and departments across the federal government, was officially established in 1990 through the U.S. Global Change Research Act (GCRA). In the subsequent years, the scope, structure, and priorities of the Program have evolved, (for example, it was referred to as the Climate Change Science Program [CCSP] for the years 2002-2008), but throughout, the Program has played an important role in shaping and coordinating our nation's global change research enterprise. This research enterprise, in turn, has played a crucial role in advancing understanding of our changing global environment and the countless ways in which human society affects and is affected by such changes.
Keywords: Environment and Environmental Studies; Earth Sciences

Review of the U.S. Global Change Research Program's Update to the Strategic Plan Document - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Update to the Strategic Plan (USP) is a supplement to the Ten-Year Strategic Plan of the U.S. Global Change Research Program (USGCRP) completed in 2012. The Strategic Plan sets out a research program guiding thirteen federal agencies in accord with the Global Change Research Act of 1990. This report reviews whether USGCRP’s efforts to achieve its goals and objectives, as documented in the USP, are adequate and responsive to the Nation’s needs, whether the priorities for continued or increased emphasis are appropriate, and if the written document communicates effectively, all within a context of the history and trajectory of the Program.
Keywords: Environment and Environmental Studies

Planning Climate and Global Change Research: A Review of the Draft U.S. Climate Change Science Program Strategic Plan - National Research Council (The National Academies Press, 2003)
Keywords: Earth Sciences

Implementing Climate and Global Change Research: A Review of the Final U.S. Climate Change Science Program Strategic Plan - National Research Council (The National Academies Press, 2004)
The report reviews a draft strategic plan from the U.S. Climate Change Science Program, a program formed in 2002 to coordinate and direct U.S. efforts in climate change and global change research. The U.S. Climate Change Science Program incorporates the decade-old Global Change Research Program and adds a new component -- the Climate Change Research Initiative -- whose primary goal is to "measurably improve the integration of scientific knowledge, including measures of uncertainty, into effective decision support systems and resources."
Keywords: Earth Sciences; Environment and Environmental Studies

Global Change Research Needs and Opportunities for 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. Global Change Research Needs and Opportunities for 2022-2031 advises the USGCRP on how best to meet its mandate in light of climate change impacts happening today and projected into the future. This report identifies critical climate change risks, research needed to support decision-making relevant to managing these risks, and opportunities for the USGCRP's participating agencies and other partners to advance these research priorities over the next decade.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Evaluating Progress of the U.S. Climate Change Science Program: Methods and Preliminary Results - National Research Council (The National Academies Press, 2007)
The U.S. Climate Change Science Program (CCSP) coordinates the efforts of 13 federal agencies to understand why climate is changing, to improve predictions about how it will change in the future, and to use that information to assess impacts on human systems and ecosystems and to better support decision making. Evaluating Progress of the U.S. Climate Change Science Program is the first review of the CCSP's progress since the program was established in 2002. It lays out a method for evaluating the CCSP, and uses that method to assess the strengths and weaknesses of the entire program and to identify areas where progress has not met expectations. The committee found that the program has made good progress in documenting and understanding temperature trends and related environmental changes on a global scale, as well as in understanding the influence of human activities on these observed changes. The ability to predict future climate changes also has improved, but efforts to understand the impacts of such changes on society and analyze mitigation and adaptation strategies are still relatively immature. The program also has not met expectations in supporting decision making, studying regional impacts, and communicating with a wider group of stakeholders.
Keywords: Earth Sciences; Environment and Environmental Studies

Accomplishments of the U.S. Global Change Research Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The U.S. Global Change Research Program (USGCRP) is an interagency program, established by the Global Change Research Act (GCRA) of 1990, mandated by Congress to "assist the Nation and the world to understand, assess, predict, and respond to human-induced and natural processes of global change". Since the USGCRP began, scientific understanding of global change has increased and the information needs of the nation have changed dramatically.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies; Earth Sciences

Enhancing Participation in the U.S. Global Change Research Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. As the understanding of global change has evolved over the past decades and as demand for scientific information on global change has increased, the USGCRP has increasingly focused on research that can inform decisions to cope with current climate variability and change, to reduce the magnitude of future changes, and to prepare for changes projected over coming decades. Overall, the current breadth and depth of research in these agencies is insufficient to meet the country's needs, particularly to support decision makers. This report provides a rationale for evaluating current program membership and capabilities and identifying potential new agencies and departments in the hopes that these changes will enable the program to more effectively inform the public and prepare for the future. It also offers actionable recommendations for adjustments to the methods and procedures that will allow the program to better meet its stated goals.
Keywords: Environment and Environmental Studies; Earth Sciences; Behavioral and Social Sciences

Restructuring Federal Climate Research to Meet the Challenges of Climate Change - National Research Council (The National Academies Press, 2009)
Climate change is one of the most important global environmental problems facing the world today. Policy decisions are already being made to limit or adapt to climate change and its impacts, but there is a need for greater integration between science and decision making. This book proposes six priorities for restructuring the United States' climate change research program to develop a more robust knowledge base and support informed responses:
Keywords: Environment and Environmental Studies; Earth Sciences